Profiling of autochthonous microbiota and characterization of the dominant lactic acid bacteria occurring in fermented fish sausages. (April 2022) - Belleggia, Luca; Ferrocino, Ilario; Rita Corvaglia, Maria; Cesaro, Cristiana; Milanović, Vesna; Cardinali, Federica; Garofalo, Cristiana; Cocolin, Luca; Aquilanti, Lucia; Osimani, Andrea
Graphical abstract: Highlights: Bacterial composition displayed the highest frequency of Latilactobacillus sakei. Mycobiota composition displayed the highest frequency of Kurtzmaniella zeylanoides. Latilactobacillus sakei and Latilactobacillus curvatus were isolated from the samples. Lactic acid bacteria isolates showed suitable traits to be used as adjunct cultures. Abstract: The use of fish flesh to produce fermented sausages is uncommon, especially in European countries where fermented sausages are mainly obtained using mammalian meat. In the present study, the microbiota naturally occurring in novel fermented fish sausages, handcrafted using marine fish species caught in the Mediterranean Sea, was studied. To this end, fish sausages were subjected to physico-chemical analyses (including histamine quantification). Microbiological traits of sausages were studied via viable counting and metataxonomic analysis. Sausages were also subjected to the detection of genes encoding histidine decarboxylase of both Gram-positive ( hdcA ) and -negative ( hdc ) bacteria. The results of histamine quantification showed different contents among fish sausage samples. Moreover, the presence of the hdcA gene was below the detection limit in all the samples, whereas the hdc gene was detected only in samples from batch 2, characterized by high levels of Enterobacteriaceae. In the analysed samples, viable lactic acid bacteria, coagulase-negative staphylococci, and eumycetes were detected. Bacterial composition displayed the highest frequency of Latilactobacillus sakei, whereas eumycetic composition displayed the highest frequency of Kurtzmaniella zeylanoides . In order to select potential adjunct cultures for product improvement, 60 lactic acid bacteria (22 isolates of L. sakei and 38 of Latilactobacillus curvatus ) were isolated from sausage samples and characterized for: i) the presence of the hdcA gene; ii) the production of exopolysaccharides (EPS); iii) the presence of genes involved in the production of EPS; iv) the production of bacteriocins against Listeria innocua . None of the isolates tested positive for the presence of the hdcA gene. Moreover, 39 out of 60 isolates showed the formation of mucoid colonies, thus attesting the production of EPS. Interestingly, 56 out of 60 isolates were positive for the gene epsD/E, whereas 37 out of 60 isolates were positive for the gene epsA, all these genes encoding the production of heteropolysaccharides. Of note, the EPS production capability and the absence of hdcA gene could represent a starting point for future selection of the isolates as autochthonous adjunct cultures to improve texture, sensory traits and safety of the fermented fish sausages under study. None of the L. sakei or L. curvatus isolates exerted a bactericidal effect against L. innocua .